Pathways to overcoming barriers to the development of telemedicine at the primary health care level in Ukraine - Riabkov, Serhii (ScienceRise: Medical Science, 2025)
The article is devoted to the analysis of barriers to the development of telemedicine at the primary health care (PHC) level in Ukraine and to the search for ways to overcome them. The study is relevant in the context of the health care reform in Ukraine launched in 2017. The aim. To analyze the barriers to the development of telemedicine at the PHC level in Ukraine and to identify pathways to overcoming them. Materials and methods. In January 2022, an online survey of 102 PHC physicians was conducted (response rate 8.5%). The questionnaire covered readiness to provide teleconsultations, technical skills, and use of medical information systems (MIS). Additional sources included data from the Ministry of Health of Ukraine, the EU4Digital Phase I (2019–2022) action plan, EU4Digital 2024 guidelines, and international experience from OECD countries. Results. Objective barriers include lack of dedicated funding for telemedicine within the National Health Service of Ukraine, weak infrastructure (65% of villages lack broadband internet; 45% of rural facilities are offline), and outdated regulations (MoH Order No. 681, 2015). Subjective barriers include psychological and cultural resistance, high physician workload, legal and ethical uncertainties, and limited trust in teleconsultations. The survey revealed that 29% of physicians had no MIS experience, but 68 % were willing to devote 2–3 hours daily to teleconsultations. 33% of physicians with over 20 years of experience demonstrated unexpected openness to adaptation. Between 2021 and 2022, the share of teleconsultations in Ukraine increased from 4.3% to 5.2% (5.7–6.9 million cases), though still far below OECD averages. Conclusions. The development of telemedicine in Ukraine is constrained by financial, infrastructural, legal, and cultural barriers. Overcoming them requires increased funding and equipment modernization, integration of remote and in-person care, digital literacy training for physicians and patients, regulatory updates, and creation of a national telemedicine platform with private sector participation. Incorporating telemedicine into the Program of Medical Guarantees represents a key opportunity for scaling